Identification and Antioxidant Activity of Flavonoids Extracted from Xinjiang Jujube (Ziziphus jujube Mill.) Leaves with Ultra-High Pressure Extraction Technology - Zhang, Li (Molecules, 2018)
In this study, the ultra-high pressure extraction (UHPE) conditions for obtaining the maximum flavonoid yield from Xinjiang jujube (Ziziphus jujuba Mill.) leaves (XJL) were optimized by response surface methodology (RSM). Box–Behnken design (BBD) was applied to evaluate the effects of four variables (extraction temperature, pressure, time and liquid-to-solid ratio) on flavonoid yield. The results showed that the optimal flavonoid yield (25.45 ± 0.21 mg/g) was derived at 50.0 °C, 342.39 MPa, 11.56 min, and a liquid-to-solid ratio of 43.95 mL/g. Eight compounds were tentatively identified and quantified as kaempferol and quercetin glycosides with UPLC-ESI-MS. Compared to ultrasound-assisted extraction (UAE), UHPE can obtain higher concentrations of total flavonoids and stronger DPPH and ABTS radical-scavenging activities in a much shorter time. Therefore, UHPE is an alternative to UAE for obtaining flavonoids from XJL, which may be an optional method for large-scale industrial flavonoid extraction from XJL.